The contribution of 'Tarbiyah' as organizational learning mechanism towards the sustainability of an Islamic-based non-governmental organization and the larger community wellbeing in Malaysia - Shaikh Ahmad, Shaikh Mansoor; Ismail, Ismi Arif; Alias, Siti Noormi (Human Resource Management Academic Research Society, 2021)
Organizational learning concept was used in developing organizations since early 20th century. Organizations are made of various communities within them. Community of Practice (CoP) are group of peoples who share a concern or a passion for something they do and learn how to do it better as they interact regularly. Organizational learning activities in the form of intellectual discourses or ‘Tarbiyah’ in the context of this study, act as a social learning input that developed activists’ mind, body and heart holistically in order for them to practice Islam as a way of life. This study employed a qualitative narrative research approach involving nine participants, six from Selangor and three from Penang Islamic-based Non-Governmental Organization. Result indicated that the ‘Tarbiyah’ affected on participants’ optimism for volunteering and self-satisfaction. It affected on their passion to contribute more as it provided a boost to their self-esteem. In essence, ‘Tarbiyah’ provide a powerful organizational learning model for this Islamic-based NGO which contributes to changes in individual and organizational behaviour. ‘Tarbiyah’ in the CoP of the NGO led individuals to co-learn, share knowledge and enrich their repertoire of becoming a better organization members and eventually enhance the larger community wellbeing.